Analisis Pengaruh Lokasi Dan Harga Terhadap Keputusan Mahasiswa Dalam Memilih Tempat Indekos Daerah Sekitar Kampus UIN Raden Intan Lampung - Yuyun Fitria; Allina Fathi Amrullah (Universitas Mitra Indonesia, 2023)
The purpose of this study was to determine the effect of location and price on student decisions in choosing boarding houses. The data used in this study were primary data. Furthermore, the data collection technique used in this study was a survey using Google forms to collect data. In this study the researchers used the f test method and coefficient test with the help of the smart plss program version 2. Based on the results of calculating the regression coefficient values for each variable, namely the R² value lies at 0 R² 1, an R² value close to 1, which means the model is getting better . Meanwhile, the value of R² which is zero means that there is no relationship between the dependent variable and the explanatory variable. From the table, with the location of R² 1 with a value of 0 1,000 1, this means that the variance of Independence is able to explain the variance of Interest in Entrepreneurship of 100 %. Keywords : Location, Price, and Student Desires